The Bookshop of Second Chances : A Novel - Fraser, Jackie, 1972- (New York : Ballantine Books, 2021)
"A woman desperate to turn a new page heads to the Scottish coast and finds herself locked in a battle of wills with an infuriatingly aloof bookseller."--
Keywords: Life change events -- Fiction; Bookstores -- Fiction; Man-woman relationships -- Fiction; Aristocracy (Social class) -- Fiction; Scotland -- Fiction; Romance fiction